Optimizing the Family Assistance Team in Reducing Stunting in Padang City Based on Environment - Rismiati Rismiati; Nurhasan Syah; Indang Dewata; Eri Barlian (Postgraduate, University of Mataram, 2024)
Based on the results of the research analysis, it can be concluded that the Family Assistance Team in reducing stunting in Padang City has performed optimally in carrying out the task of reducing stunting in Padang City. There are obstacles encountered by the Family Assistance Team in carrying out their duties, namelyoften changing midwives, it is difficult to adjust the data collection schedule, looking for families who are registered with the family assistance team but are not domiciled,There are several families who are not open to accepting us to visit their homes, the application often has errors, the public's awareness of checking their health is still low, the dual task of being an employee and the duties of the family assistance team, families not implementing the recommendations of the family assistance team.